Implementasi Aplikasi Penggajian Karyawan Pada PT. Kemasan Cipta Utama Berbasis VB.Net - Hasmizal Hasmizal; Arif Maulana Yusuf; Yeny Rostiani; Syaraswati Syaraswati (Jurnal Accounting Information System (AIMS), 2022)
PT. Ciptatama Perfect Packaging (KCS) was founded in 1995 starting from the production of styrofoam by prioritizing customer satisfaction, PT. Packaging Cipta Utama has human resources in this case employees who are divided into 2 (two) namely permanent employees and contract employees. The purpose of this study was to analyze and design a computer-based payroll system at PT. Cipta Utama packaging using Microsoft Visual Studio 2008. The research method used is SDLC (System Development Life Cycle) with a waterfall approach model that starts with system analysis, system design, program code generation and testing. PT. Cipta Utama packaging in processing payroll data still uses Microsoft Excel. All payroll calculation activities are carried out manually based on documents related to employee salary calculations. This study discusses the payroll system starting from the document. The object of research uses a computerized payroll system, performs analysis and makes applications using the Microsoft Visual Studio 2008 programming language so that it provides a lot of efficiency and effectiveness in processing payroll. With the payroll system at PT. It is hoped that the management of Cipta Utama can improve the company's internal control.